The beach bum [videorecording (DVD)] - Korine, Harmony; Korine, Harmony; McConaughey, Matthew, 1969-; Snoop Dogg, 1972-; Fisher, Isla, 1976- (Universal Pictures Home Entertainment, 2019)
Follows the misadventures of Moondog who is slowly writing a new book while living in the Florida Keys.